Production of porous stainless steel using the space holder method - Tan, Koon Tatt; Norhamidi Muhamad,; Andanastuti Muchtar,; Abu Bakar Sulong,; Kok, Yih Shia (Penerbit Universiti Kebangsaan Malaysia, 2021)
Metallic foams and porous materials can be produced by various methods. Among the methods that can produce metallic foams and porous materials, powder metallurgy is a promising method. This study investigates the production of a porous stainless steel by the space holder method in powder metallurgy. A novel space holder i.e. glycine and binder consisting of polymethylmethacrylate and stearic acid are used. Different amounts of glycine are added to the mixture of stainless-steel powder and binder. Subsequently, each mixture is cold-pressed at a pressure of 9-ton m-2. The samples are sintered at 1050 and 1150 °C with holding times of 30, 60, and 90 min. The microstructures and physical and mechanical properties of the sintered samples are investigated. A porous stainless steel with porosity ranging from 30.8 to 51.4% is successfully fabricated. Results show that the glycine content and sintering parameters influence the properties of the porous stainless steel. The sintering temperature significantly affects volumetric shrinkage. Volumetric shrinkage decreases as the volume fraction of glycine increases to 30% whereas sintering temperature 1150 °C and holding time 90 min will increase the volumetric shrinkage. The compressive yield strength and corresponding elastic modulus are in the ranges of 22.9 to 57.6 MPa and 6.3 to 26.8 GPa, respectively. The samples produced have potential biomedical applications because their mechanical properties, yield strength and elastic modulus match those of human bones.